(untitled) (Bangladesh Journal of Urology, 2022)
Spontaneous nephrocutaneous fistula is a very rare entity. The majority of causes are:post operative, calculus pyonephrosis, chronic pyelonephritis, renal infection, perinephric abscess, trauma. Renal tumor, xanthogranulomatous pyelonephritis (XGP) and renal tuberculosis. A case of spontaneous nephrocutaneous fistula in a 32 years young lady complaining of seropurulent discharge from the fistula over the right lumber flank for last 8 months is presented and discussed here. Brief history, physical examination. Ultrasonography. CT fistulogramwere performed which revealed an active fistula tract from skin to pelvicalyceal system of right kidney with a large impacted stone at right pelviureteric junction (PUJ). Patient was nondiabetic and negative for renal tuberculosis whereas renogram showed 32% relative renal function of the affected side. We performed exploration along with excision of the fistula tract, partial nephrectomy, pylolithotomy with DJ stenting and percutaneous nephrostomy (PCN). Follow up period was grossly uneventful. Currently, the occurrence of these types of spontaneous fistula is extremely rare except in patient with uncontrolled DM, neoplasia or immunosuppression in general. Bangladesh J. Urol. 2021; 24(2): 235-238